Treatment of sudden sensorineural hearing loss with hyperbaric oxygenation – our experience - Živaljević, Zvonko M; Živić, Ljubica; Mihailović, Nataša; Živković, Miodrag; Vorkapić, Branko; Baletić, Nenad (Vojnosanitetski pregled, 2017)
Background/Aim. Sudden sensorineural hearing loss is manifested by the loss of hearing for more than 30 dB at three consecutive frequencies in the timeframe of 72 h. It is of unclear etiology and pathogenesis, which leads to the use of different therapeutic methods. Treatment protocols are not compliant, making it difficult to objectively quantify their impact. The aim of this study was to show the effect of hyperbaric oxygen therapy as the only method for the treatment of sudden sensorineural hearing loss. Methods. This retrospective study included 20 patients treated for sudden sensorineural hearing loss with hyperbaric oxygenation (HBO) in the period from 2004 to 2014. The study was conducted in the specialized medical clinic for hyperbaric and underwater medicine, HBO Medical Center in Belgrade. The patients were treated according to the following protocol: a session of 60 min at the pressure of 2 bars (2ATA) two times a day, a total of 30 sessions. Assessment of the therapy effects was performed by observing the change in the hearing threshold at the frequencies of 500, 1,000, 2,000 and 4,000 Hz at the end of the treatment. Results. After the completion of treatment according to the protocol, a full hearing recovery (total improvement of hearing damage or achieving final hearing threshold above 25 dB) was found in 11 (55%) of the patients. A partial recovery (hearing improvement of up to 15 dB, and a final hearing threshold below 45 dB) occurred in 4 (20%) of the patients. In 5 (25%) of the patients, improvement was not verified (there was no recovery or it was less than 5 dB). The average absolute hearing recovery was 24.94 dB. The mean relative hearing recovery was 65.45%. Conclusion. Because of the unclear multifactorial etiopathogenesis of this disease, there are many therapeutic protocols. Based on the results of our study HBO therapy could be recommended primarily as the treatment for sudden sensorineural hearing loss.